FORMULASI PUPUK CAIR Pseudomonas fluorescens SEBAGAI AGENSIA PENGENDALI HAYATI PENYAKIT MOSAIK TANAMAN KAKAO - Wiwit Probowati; Pilar Rosatria Firyalunfah; Wahyuni Wulansari (Universitas Tidar, 2020)
Cocoa is a strategic commodity for plantation in Indonesia. However, pest and disease infections are inevitably common constrains for the cocoa cultivators. Cocoa mosaic disease is one of disease which is cause cocoa trees suffering. Pseudomonas fluorescens are obligate aerobic bacteria that are very valuable for agricultural technology. The bacteria also protect plants from pathogens infection by producing secondary metabolites that kill bacteria and other fungi. The bacteria can use as safe and environmentally friendly biological control agents. This study aims to determine P. fluorescens liquid fertilizer formulation and its effectiveness in suppressing mosaic disease in cocoa plants. The research method was carried out by making a liquid formula from P. fluorescens and then applying it to cocoa plants that were attacked by mosaic disease. Bacteria isolates grown in conch broth medium were incubated for 3 days. Then the fertilizer formula was applied to mosaic symptomatic cocoa plants with fertilizer concentrations of 25%, 50% and 75% compared to spraying using chemical insecticides. The results showed that the liquid formula concentration of 75% can suppress the most effective mosaic symptoms and the optimal growth of cocoa plants for 7 treatments.. Keywords: Cocoa, Formulation, mosaic disease, Pseudomonas fluorescens